2019
DOI: 10.1038/s41380-018-0329-5
|View full text |Cite
|
Sign up to set email alerts
|

The importance of buprenorphine research in the opioid crisis

Abstract: With the urgency to treat patients more effectively for opioid use disorder in the midst of the opioid epidemic, a key area for precision medicine is to improve individualized medication-assisted treatment for opioid use disorder. The expansion of medication-assisted treatment is a key to reducing illicit opioid use, preventing opioid overdose deaths, and reducing the comorbidities and societal impacts of opioid use disorder. The most common medication for opioid use disorder will soon be buprenorphine. Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Buprenorphine is a μ-opioid receptor partial agonist and κ-opioid receptor antagonist that is commonly used to treat opioid use disorder. It also exerts antidepressant and anxiolytic activity and is a promising treatment for neonatal opioid withdrawal syndrome 110 . A retrospective cohort study showed that 6-month treatment retention rates and opioid abstinence rates were not different between individuals who were positive for fentanyl or heroin at baseline before initiating buprenorphine treatment, indicating that buprenorphine may still be beneficial for treating fentanyl exposure 111 .…”
Section: Interventions For the Management And Prevention Of Fentanyl mentioning
confidence: 99%
“…Buprenorphine is a μ-opioid receptor partial agonist and κ-opioid receptor antagonist that is commonly used to treat opioid use disorder. It also exerts antidepressant and anxiolytic activity and is a promising treatment for neonatal opioid withdrawal syndrome 110 . A retrospective cohort study showed that 6-month treatment retention rates and opioid abstinence rates were not different between individuals who were positive for fentanyl or heroin at baseline before initiating buprenorphine treatment, indicating that buprenorphine may still be beneficial for treating fentanyl exposure 111 .…”
Section: Interventions For the Management And Prevention Of Fentanyl mentioning
confidence: 99%
“…There are some authors of scientific publications claiming that an adequate opioid blockade requires an 'optimal exposure' with BUP plasma concentrations of 2-3 ng/ mL and that this is achieved with a daily sublingual (SL) dose of BUP or buprenorphine/naloxone (BUP-NLX) of 16 mg and higher [5][6][7]. However, others suggest that further research is needed to understand dose-response relationships in patients with this complex disorder [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Buprenorphine is a commonly used opiate agonist treatment (OAT) 14 . It is a partial agonist of the μ, and a full antagonist of the κ, opioid receptor 15,16 .…”
Section: Introductionmentioning
confidence: 99%